Implementation of A Nationwide Health Economic Consultation Service to Assist Substance Use Researchers: Lessons Learned. Issue 2 (April 2018) - Murphy, Sean M.; Leff, Jared A.; Linas, Benjamin P.; Morgan, Jake R.; McCollister, Kathryn; Schackman, Bruce R.
Background: Health economic evaluation findings assist stakeholders in improving the quality, availability, scalability, and sustainability of evidence-based services, and in maximizing the efficiency of service delivery. The Center for Health Economics of Treatment Interventions for Substance Use Disorders, HCV, and HIV (CHERISH) is a NIDA-funded multi-institutional center of excellence whose mission is to develop and disseminate health-economic research on healthcare utilization, health outcomes, and health-related behaviors that informs substance use disorder treatment policy, and HCV and HIV care of people who use substances. Methods: We designed a consultation service that is free to researchers whose work aligns with CHERISH's mission. The service includes up to six hours of consulting time. After prospective consultees submit their request online, they receive a screening call from the consultation service director, who connects them with a consultant with relevant expertise. Consultees and consultants complete web-based evaluations following the consultation; consultees also complete a six-month follow-up. We report on the status of the service from its inception in July 2015 through June 2017. Results: We have received 28 consultation requests (54% Early Stage Investigators, 57% MD or equivalent, 28% PhD, 61% women) on projects typically related to planning a study or grant application (93%); 71% were HIV/AIDS-related. Leading topics included cost-effectiveness (43%), statistical-analysis/econometrics (36%), cost (32%), cost-benefit (21%), and quality-of-life (18%). All consultees were satisfied with their overall experience, and felt that consultation expectations and objectives were clearly defined and the consultant's expertise was matched appropriately with their needs. Results were similar for consultants, who spent a median of 3 hours on consultations. Conclusions: There is a need for health-economic methodological guidance among substance use, HCV, and HIV researchers. Lessons learned pertain to the feasibility of service provision, the need to implement systems to measure and improve service value, and strategies for service promotion.